ISPC Commentary on Synthesis Report - Urbanization and Farm Size - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
The synthesis report identifies six conclusions, from which it derives six corresponding recommendations. For the most part, the ISPC endorses these conclusions and recommendations. Each of these is summarized in the commentary, followed by specific comments from the ISPC.